2021
DOI: 10.1016/j.ajogmf.2021.100403
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine acceptance among pregnant, breastfeeding, and nonpregnant reproductive-aged women

Abstract: Background Although mass vaccination against COVID-19 may prove to be the most efficacious end to this deadly pandemic, there remains concern and indecision among the public towards vaccination. As pregnant and reproductive-aged women account for a large proportion of the population with particular concerns regarding vaccination against COVID-19, this survey aims at investigating their current attitudes and beliefs within our own institution. Objective To understand vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
161
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(185 citation statements)
references
References 7 publications
16
161
6
2
Order By: Relevance
“… 23 – 25 However, the finding is much lower when compared with previous studies conducted in different countries. 1 , 26 29 The discrepancy in the above finding might be attributable to the study setting difference where our study employed face-to-face interviews, whereas the other studies were web-based surveys. Besides, since our study participants were pregnant women, more negative responses could occur as pregnant women might have apprehension of vaccine effect on pregnancy.…”
Section: Discussionmentioning
confidence: 85%
“… 23 – 25 However, the finding is much lower when compared with previous studies conducted in different countries. 1 , 26 29 The discrepancy in the above finding might be attributable to the study setting difference where our study employed face-to-face interviews, whereas the other studies were web-based surveys. Besides, since our study participants were pregnant women, more negative responses could occur as pregnant women might have apprehension of vaccine effect on pregnancy.…”
Section: Discussionmentioning
confidence: 85%
“…A recent study conducted in the United States among a similar study population that explored COVID-19 vaccination acceptance among pregnant, non-pregnant and breastfeeding women reported that non-pregnant women were most likely to accept vaccination (76.2%), with breastfeeding women the second most likely to accept vaccination (55.2%); pregnant women had the lowest rate of vaccine acceptance (44.3%). 40 Another study in the US conducted on 939 pregnant women reported that only 41% of the participants would get a vaccine, and 82.0% of the participants were concerned about vaccine safety for their pregnancy. 41 This study showed that pregnant women and those planning to get pregnant had higher scores of hesitancy regarding taking the vaccine in comparison to women who are not pregnant or not planning to be pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…42 Previous studies investigating the acceptance of taking the COVID-19 vaccine have shown similar results. 30,40,[43][44][45] One study conducted in Turkey in 2021 reported a lower rate of COVID-19 vaccine acceptability, with only 37% stating that they intend to receive the vaccine if it were recommended for pregnant women. 45 Similar results were reported in a large study that included 16 countries across the world, with only 52.0% of pregnant women reporting that they will take the vaccine compared to 73.4% of nonpregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have been documented that include Spanish speakers and compare results across language groups. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%